1997
DOI: 10.1379/1466-1268(1997)002<0012:htipmh>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Hsp30, the integral plasma membrane heat shock protein of Saccharmyces cerevisiae, is a stress-inducible regulator of plasma membrane H+-ATPase

Abstract: Saccharomyces cerevisiae has a single integral plasma membrane heat shock protein (Hsp). This Hsp30 is induced by several stresses, including heat shock, ethanol exposure, severe osmostress, weak organic acid exposure and glucose limitation. Plasma membrane H(+)-ATPase activities of heat shocked and weak acid-adapted, hsp30 mutant and wild-type cells, revealed that Hsp30 induction leads to a downregulation of the stress-stimulation of this H(+)-ATPase. Plasma membrane H(+)-ATPase activity consumes a substantia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
161
1

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(166 citation statements)
references
References 0 publications
3
161
1
Order By: Relevance
“…Although we were unable to detect a significant, measurable decline in pH, in response to sorbic acid, evidence suggests that this does occur but that increased activation of the mem-(0 1998 The Society brane H+-ATPase, which is known to occur on exposure to weak acids (Holyoak etal. 1996;Piper et al 1997;Viegas etal. 1998), may have resulted in the restoration of pH, homeostasis such that any fluctuation became undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…Although we were unable to detect a significant, measurable decline in pH, in response to sorbic acid, evidence suggests that this does occur but that increased activation of the mem-(0 1998 The Society brane H+-ATPase, which is known to occur on exposure to weak acids (Holyoak etal. 1996;Piper et al 1997;Viegas etal. 1998), may have resulted in the restoration of pH, homeostasis such that any fluctuation became undetectable.…”
Section: Discussionmentioning
confidence: 99%
“…[30] H + -ATPase is, however, also a key activity for counteracting weak organic acid stress, becoming strongly activated whenever cells are exposed to monocarboxylate preservatives. [12,26] Physiological studies have revealed that the acids in Figure 1a do not all act identically on S. cerevisiae, the more lipophilic ones being much more effective inhibitors of growth. [11,25,37] Side-byside comparisons of the effects of acetic and sorbic acids (acids of identical pKa) show that it requires quite high acetic acid level (80-150 mM) in order to inhibit pH 4.5 cultures of glucose-repressed S. cerevisiae, whereas only 1-3 mM of the more liposoluble sorbic acid achieves the same degree of growth inhibition.…”
Section: A Brief Overview Of the Physiological Actions Of The Monocarmentioning
confidence: 99%
“…[1,19,36] Therefore, while acetic acid may largely inhibit cells by generating a high intracellular pool of acetate anion and the lowering of intracellular pH (Figure 1b), the cytostatic effects of sorbic acid are suggested to be mainly due to its disordering of membrane structure. [2,36] High acetic acid is a potent inducer of yeast apoptosis; [6,[14][15][16] whereas the noted actions of benzoic and sorbic acids include a severe energy (ATP pool) depletion, [26] an inhibition of membrane trafficking, resulting in the arrest of macroautophagy [8] and, in the presence of oxygen, severe oxidative stress due to elevated endogenous production of reactive oxygen species (ROS) by a dysfunctional mitochondrial respiratory chain. [25] It is now known that acetic acid and sorbic acid, at these respective inhibitory concentrations, induce quite separate stress responses in pH 4.5 cultures of S. cerevisiae; one protective against acetic acid stress and another protective against the more lipophilic propionate, sorbate and benzoate (Table 1).…”
Section: A Brief Overview Of the Physiological Actions Of The Monocarmentioning
confidence: 99%
“…However, from these studies a model emerged that weak acids trigger a two-step process of adaptation and assimilation. Piper et al (1997Piper et al ( , 1998 have shown that sorbic acid, ethanol and heat shock induce two plasma membrane proteins, Hsp30p and Pdr12p, in the yeast Saccharomyces cerevisiae. Hsp30p is involved in adaptation to weak acid by regulating the activity of the membrane H + -ATPase (Braley & Piper, 1997;Piper et al, 1997).…”
Section: Introductionmentioning
confidence: 99%